Optimal Timing of Percutaneous Transhepatic Gallbladder Drainage in High-Risk Acute Cholecystitis Patients and Its Impact on Elective Laparoscopic Cholecystectomy - Sakarie Mustafe Hidg; Hannan Samatar (RGUHS Journal of Medical Sciences)
Aim To compare the effect of the timing of Percutaneous Transhepatic Gallbladder Drainage PTGBD intervention on the difficulty of elective Laparoscopic cholecystectomy LC in high-risk patients with acute cholecystitis.Methods A retrospective analysis was used to collect data from the First Affiliated Hospital of Xinjiang Medical University. Clinical data of patients treated for acute cholestatic PTGBD between 2017 and 2022 was collected. Thirty cases were included in the early intervention group le2 days and 36 cases in the late intervention group gt2 days. The reasons for tube placement tube placement-related complications surgical difficulty and postoperative pathological findings were compared between the two groups.Results There were no statistically significant differences between the two groups in terms of age at admission or comorbidities. However significant differences were observed in complications related to time P0.001 intraoperative blood loss P0.017 severe adhesions P0.001 and the conversion rate to open surgery P0.042. The Spearmans correlation coefficient between the interval time from onset and conversion was 0.25 P0.043.Conclusion PTGBD performed within two days of symptom onset may reduce the difficulty of surgery. The conversion in performing LC after PTGBD in patients with acute cholecystitis is positively correlated with the time between performing PTGBD.